Nitrated Nucleotides: New Players in Signaling Pathways of Reactive Nitrogen and Oxygen Species in Plants - Petřivalský, Marek; Luhová, Lenka (Frontiers in Plant Science, 2020)
Nitration of diverse biomolecules, including proteins, lipids and nucleic acid, by reactive nitrogen species represents one of the key mechanisms mediating nitric oxide (NO) biological activity across all types of organisms. 8-nitroguanosine 3',5'-cyclic monophosphate (8-nitro-cGMP) has been identified as a unique electrophilic intermediate involved in intracellular redox signalling. In animal cells, 8-nitro-cGMP is formed from the guanine nucleotide pool by a combined action of NO, reactive oxygen species (ROS) and guanylate cyclase. As demonstrated originally in animal models, 8-nitro-cGMP shows certain biological activities closely resembling its analogue cGMP; however, its regulatory functions are mediated mainly by its electrophilic properties and chemical interactions with protein thiols resulting in a novel protein post-translational modification termed S-guanylation. In Arabidopsis thaliana, 8-nitro-cGMP was reported to mediate NO-dependent signalling pathways controlling abscisic acid (ABA)-induced stomatal closure; however, its derivative 8-mercapto-cGMP (8-SH-cGMP) was later shown as the active component of hydrogen sulphide (H2S)-mediated guard cell signalling. Here we present an overview of current knowledge on formation, metabolism and biological activities of nitrated nucleotides with special attention to described and proposed functions of 8-nitro-cGMP and its metabolites in plant physiology and stress responses.